0913 Ambulatory Blood Pressure Monitoring In Children With Obstructive Sleep Apnea Syndrome. (27th May 2020) - Geng, X; Wu, Y; Ge, W; Feng, G; Zheng, L; Xu, Z; Ni, X
Abstract: Introduction: This study was performed to investigate the differences in blood pressure among different groups of snoring children and among different sleep stages.In recent years, the incidence of OSAS in children has increased year by year. Blood pressure research of OSAS children can better understand the occurrence of OSAS related complications. Early detection and intervention of blood pressure changes in children with OSAS can effectively reduce the incidence of cardiovascular disease in adulthood and lower the disease burden. Methods: Habitually snoring children (snoring frequency of ≥3 nights per week) aged 3to 11 years were recruited from Beijing Children's Hospital, Capital Medical University from 1 January 2017 to 30 June 2018. All children underwent polysomnography, and their blood pressure was monitored and calculated by the pulse transit time. The children were divided into those with primary snoring (PS), mild obstructive sleep apnea syndrome (OSAS), and moderate to severe OSAS according to their obstructive apnea-hypopnea index (OAHI). Results: In total, 140 children were recruited. Ninety-seven had PS, 24 had mild OSAS, and 19 had moderate to severe OSAS. There were no differences in age, sex, or body mass index z-score among the groups. Statistically significant differences were found in the OAHI, oxygen desaturation index 3%, respiratory arousal index, and lowest oxygen saturation among the three groups. Children with moderate to severe OSAS had higher systolic and diastolic blood pressure than those with mild OSAS and PS (P < 0.001). In all children, systolic and diastolic blood pressure was higher in the rapid eye movement (REM) sleep stage than in the non-REM sleep stage (P < 0.05). Conclusion: Children with moderate to severe OSAS had higher blood pressure than those with PS and mild OSAS. Blood pressure in the REM sleep stage was higher than that in other sleep stages in all groups of children. Support: The Pediatric Medical Coordinated Development Center of Beijing Hospitals Authority (XTYB201807);Capital Health Research and Development of Special Funding (2018-1-2091);National Key Research and Development Plan (2017YFC0112502)